1997
DOI: 10.1002/(sici)1096-9861(19970623)383:1<18::aid-cne2>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Afferent and efferent connections of the diencephalic prepacemaker nucleus in the weakly electric fish,Eigenmannia virescens: interactions between the electromotor system and the neuroendocrine axis

Abstract: The afferent and efferent connections of the gymnotiform central posterior nucleus of the dorsal thalamus and prepacemaker nucleus (CP/PPn) were examined by retrograde and anterograde transport of the small molecular weight tracer, Neurobiotin. The CP/PPn was identified by physiological assay and received a local iontophoretic injection of Neurobiotin. Retrogradely labeled somata were observed in the ventral telencephalon, hypothalamus, and the pretectal nucleus electrosensorius. Anterogradely labeled fibers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 82 publications
(113 reference statements)
3
32
1
Order By: Relevance
“…The Journal of Experimental Biology (2014) include telencephalic regions (Braithwaite, 2005) that are likely homologous with the mammalian pallium and basal ganglia (Wong, 1997;Harvey-Girard et al, 2012;Harvey-Girard et al, 2013). A recent paper (Pereira et al, 2014) has demonstrated that when the telencephalon of Gymnotus omarum is ablated the fish remains quiescent and does not initiate movement for the duration of lengthy experiments.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…The Journal of Experimental Biology (2014) include telencephalic regions (Braithwaite, 2005) that are likely homologous with the mammalian pallium and basal ganglia (Wong, 1997;Harvey-Girard et al, 2012;Harvey-Girard et al, 2013). A recent paper (Pereira et al, 2014) has demonstrated that when the telencephalon of Gymnotus omarum is ablated the fish remains quiescent and does not initiate movement for the duration of lengthy experiments.…”
Section: Research Articlementioning
confidence: 99%
“…Pulse-type electro-sensation thus offers a distinct experimental advantage because each sampling event can be readily and non-invasively monitored from an unrestrained animal (Jun et al, 2012;Jun et al, 2014). In gymnotiform species, EOD pulses are directly driven by a hindbrain pacemaker that is modulated by diencephalic and medullary prepacemaker activity (Heiligenberg et al, 1981;Kawasaki et al, 1988;Dye, 1988;Metzner, 1993;Caputi et al, 1993;Zupanc and Maler, 1997;Wong, 1997;Comas and Borde, 2010). Previous studies of the electromotor circuitry (Caputi et al, 1993;Wong, 1997;Giassi et al, 2012), functional stimulation of an electromotor thalamic nucleus (Comas and Borde, 2010) and drug injection in the pallium (Santana et al, 2001) all indicate a strong modulation of the EODR from the forebrain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, pulse-type species exhibit more variable EOD rate compared to the wave-type species; and animals' EOD rates closely reflect novelty contents of their sensory surroundings 17,18 . Temporal modulations in the EOD rate can reveal higher-level neural activities, since the medullary pacemaker receives direct neural inputs from higher brain regions such as the diencephalic prepacemaker nucleus, which in turn receives axonal projections from the forebrain 19 . However, the EOD timing must be carefully extracted from a raw waveform recording and not biased by the animal's movement-induced distortions.…”
Section: Introductionmentioning
confidence: 87%
“…Over this period, the EODR creates a complex, bimodal time series that correlates strongly with the movement variable (Fig. 1) and that carries information on neural activity descending from the higher brain centers (Wong, 1997; Giassi et al, 2012a). An adequate model for the EODR would thus give us the ability to characterize, on a phenomenological level, the neural control process underlying spontaneous movement initiation and termination in naturally behaving fish.…”
Section: Methodsmentioning
confidence: 99%